2017
DOI: 10.3791/56095
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Chronic Obstructive Pulmonary Disease Model in Mice by Repeated Ozone Exposure

Abstract: Chronic obstructive pulmonary disease (COPD) is characterized by persistent airflow limitation and lung parenchymal destruction. It has a very high incidence in aging populations. The current conventional therapies for COPD focus mainly on symptom-modifying drugs; thus, the development of new therapies is urgently needed. Qualified animal models of COPD could help to characterize the underlying mechanisms and can be used for new drug screening. Current COPD models, such as lipopolysaccharide (LPS) or the porci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Ozone exposure has been shown to disrupt largeairway function in mice. 9,19,20 Similarly, we have shown that ozone exposure can induce a decline in FEV50.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Ozone exposure has been shown to disrupt largeairway function in mice. 9,19,20 Similarly, we have shown that ozone exposure can induce a decline in FEV50.…”
Section: Discussionmentioning
confidence: 56%
“…Ozone exposure has been shown to disrupt large-airway function in mice. 9 , 19 , 20 Similarly, we have shown that ozone exposure can induce a decline in FEV50. Furthermore, in the present study, we emphasized the impairment of small-airway function in mouse models of asthma.…”
Section: Discussionmentioning
confidence: 60%
“…The H&E sections were observed under a 200× magni cation optical microscope, and 10 peripheral visual elds were randomly taken from each section. The images of the sections were opened in Photoshop, a cross line was drawn through the positive center of the image (avoiding the elds of airways and vessels as much as possible), the number of alveolar spaces (n) that passed through these two lines were counted, and the total length of the cross line (L) was measured, which was calculated using the formula, Lm = L / N. The value represents the average alveolar diameter, re ects the degree of alveolar damage [16].…”
Section: Mean Linear Intercept (Lm)mentioning
confidence: 99%
“…42,43 In a recent development, researchers have even generated a new COPD mouse model by exposing mice to high levels of ozone. 44 All of these methods are increasing in accuracy and precision and are valuable in many contexts. However, it is also known that the methods to generate the disease model will, by their very nature, change the course of the disease, not just in onset, but in terms of features and phenotypes, progression, and lethality, with unknown effects on eventual generalizability, or lack thereof, to the corresponding human disease.…”
Section: Animal Model Limitationsmentioning
confidence: 99%